Impact of Brexit on construction stocks listed on Bursa Malaysia - Senthil Kumar, T.; Mohd Ridzuan, Darun; Mohammad, Aslam (KnE Social Sciences, 2019)
The British exit from the European Union (Brexit) referendum conducted in the United Kingdom (UK) about remaining in the European Union (EU) has had a profound effect on the world economy. Stock markets across the globe bore the brunt and pound sterling weakened sharply on this announcement. However, not all the economies were affected in the same way and the effect ranged from no impact to high impact. Economies which had considerable exposure to the UK, were affected. Though Malaysia does not have highly significant trade connections with the UK, the construction sector has moderate exposure to UK investments. In this study, construction companies’ stock price movement during the Brexit announcement was analyzed using the Event Study Methodology. Ten publicly traded construction companies were randomly selected and their stock returns were compared with the KCI Market Index returns. The returns were very volatile and showed a negative trend during the first few days around the Brexit announcement indicating that there was an insignificant short-term impact. However, the shock was quickly absorbed and the stock returns stabilized in a few days implying that the Brexit announcement did not have a significant long-term impact on construction company stocks in Malaysia.